The Tulsa reader : 1971-2010 - Clark, Larry ([New York] : [Chelsea Spengemann], 2010)
The work compiles photocopied reproductions of the extensive material--interviews, articles, press releases, gallery memos, letters to the editor--surrounding Larry Clark's controversial photo series, Tulsa, first exhibited and concurrently published as the iconic artist book in 1971. The hundreds of write-ups and other material gathered in the reader act as a record of Tulsa's extended life and impact, but also form a collage work in its own right. The repetition of images from the series, most often the well-known photo of a youth seated shirtless and cross-legged with a pistol in hand lends the work a compulsive feel suited to the degraded, addictive work it describes
boek
Keywords: Clark, Larry